Hyperthermia and radiotherapy in bladder cancer. (18th May 2016) - Snider, James William; Datta, Niloy Ranjan; Vujaskovic, Zeljko
Abstract: Hyperthermia represents a unique, safe, and advantageous methodology for improving therapeutic strategies in the management of bladder cancer. This modality has shown promise in contributing to treatment regimens for both superficial and muscle-invasive disease. Especially in conjunction with intravesical chemotherapy, systemic therapy, and radiotherapy, hyperthermia shows particular synergistic benefit. As such, it should be explored further through clinical use and clinical trial in conjunction with currently available techniques and emerging technologies. However, to conceptualise the way forward, it is particularly important to understand the current challenges to widespread use of non-invasive, bladder-sparing approaches and the current state of bladder cancer care. As such, in the following article, we have focused on not only the rationale for concurrent radiotherapy and hyperthermia, but also the clinical landscape in bladder cancer as a whole.